2021
DOI: 10.3390/s21248414
|View full text |Cite
|
Sign up to set email alerts
|

A New Socially Assistive Robot with Integrated Serious Games for Therapies with Children with Autism Spectrum Disorder and Down Syndrome: A Pilot Study

Abstract: This work introduces a new socially assistive robot termed MARIA T21 (meaning “Mobile Autonomous Robot for Interaction with Autistics”, with the addition of the acronym T21, meaning “Trisomy 21”, which is used to designate individuals with Down syndrome). This new robot is used in psychomotor therapies for children with Down syndrome (contributing to improve their proprioception, postural balance, and gait) as well as in psychosocial and cognitive therapies for children with autism spectrum disorder. The robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…The paper [47] introduces a newly developed socially assistive robot (MARIA T21) used in psychomotor therapies for children with Down syndrome and psychosocial and cognitive therapies for children with ASD. The authors describe a pilot study with serious games in four stages and highlight the children's emotional interplay with the robot, and it is observed that the robot MARIA T21 demonstrates notable gain in the field of assistive robotics.…”
Section: Related Work On Interactive Scenarios With Social Robots For...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper [47] introduces a newly developed socially assistive robot (MARIA T21) used in psychomotor therapies for children with Down syndrome and psychosocial and cognitive therapies for children with ASD. The authors describe a pilot study with serious games in four stages and highlight the children's emotional interplay with the robot, and it is observed that the robot MARIA T21 demonstrates notable gain in the field of assistive robotics.…”
Section: Related Work On Interactive Scenarios With Social Robots For...mentioning
confidence: 99%
“…The participants in this scenario are the social robot and eight children, supervised by the therapist and a group of researchers. Activity description [47], page 6-14 (see in Section 5 Methodology)…”
Section: Participants' Role and Behaviormentioning
confidence: 99%
“…Robots can provide these services during epidemics without the risk of transmitting infection. In addition, children with autism communicate more engagingly and have better social behaviors with robots than with human trainees[ 78 , 79 ].…”
Section: Indirect Impact Of Covid-19mentioning
confidence: 99%
“…The development of this robot is mainly based on the article by Flores et al [ 4 ]. However, the proposals of [ 5 , 6 , 7 , 8 , 9 ] were reviewed to complement and improve this prototype.…”
Section: Introductionmentioning
confidence: 99%